The visual display of quantitative information - Tufte, Edward R. 1942- (Graphics Press, 2001)
This book deals with the theory and practice in the design of data graphics and makes the point that the most effective way to describe, explore, and summarize a set of numbers is to look at pictures of those numbers, through the use of statistical graphics, charts, and tables. It includes 250 illustrations of the best (and a few of the worst) statistical graphics, with detailed analysis of how to display data for precise, effective, quick analysis. Also offered is information on the design of the high resolution displays, small multiples, editing and improving graphics, and the data ink ratio. Time series, relational graphics, data maps, multivariate designs, as well as detection of graphical deception: design variation vs. data variation, and sources of deception are discussed. Information on aesthetics and data graphical displays is included. The 2nd edition provides high resolution color reproductions of the many graphics of William Playfair (1750-1800), adds color to other images where appropriate, and includes all the changes and corrections during the 17 printings of the 1st edition.